Depositing memory. From the museum-warehouse to the storage - Federica Visconti (Festival dell'Architettura Magazine, 2020)
The paper aims to analyse the idea of ‘museum as storage’ proposed by Louis Kahn in the unbuilt project for the de Menil Foundation in Texas preceded by the constructions for Yale University in Connecticut and of the Kimbell Art Museum in Fort Worth. By analysing the etymological meaning of the word ‘storage’ (in Italian, deposito) as the act or the place for preservation and transmission of the memory, a link is established with some contemporary phenomena in the era of the World Wide Web and, in particular, with the work of musealization of architecture and the city proposed by the British director Peter Greenaway, in order to finally question, also in the digital age, the need of the space for the representation of the values of a community.